North‐west Africa as a source and refuge area of plant biodiversity: a case study on Campanula kremeri and Campanula occidentalis. (17th April 2017) - García‐Aloy, Sara; Vitales, Daniel; Roquet, Cristina; Sanmartín, Isabel; Vargas, Pablo; Molero, Julián; Kamau, Peris; Aldasoro, Juan José; Alarcón, Marisa
Abstract: Aim: North‐west Africa, because of its position at the crossroads between Macaronesia and the Iberian Peninsula, has played an important role on the emergence and maintenance of Mediterranean plant diversity. In this study, we reconstruct the phylogeographical history of a lineage of bellflowers comprising the north African‐south Iberian species Campanula kremeri and the Canarian Campanula occidentalis ( Azorina ‐group), to investigate the genetic imprints left by past climatic and palaeogeographical events on the northern African flora. Location: North‐west Africa, Iberian Peninsula, and the Canary Islands. Methods: We reconstructed the biogeographical history of the Azorina ‐group to provide a phylogenetic background. We then investigated the phylogeographical patterns within C. kremeri and C. occidentalis using the AFLP and sequence data. We integrated these results with the past species‐distribution modelling to understand the current biodiversity patterns within this lineage. Results: The ancestor of C. kremeri ‐ C. occidentalis diverged in the Late Miocene/Early Pliocene. Nuclear data supported species monophyly, whereas plastid data suggested that C. kremeri is paraphyletic. Maghrebian populations of C. kremeri showed high genetic diversity, whilst Iberian ones and those of C. occidentalis exhibited lower values. Main conclusions: Repeated expansion‐retraction events associated with Pleistocene climatic changes in North Africa facilitated gene flow across Maghrebian ranges in C. kremeri . Mountain massifs in north‐west Africa likely acted as refugia for Mediterranean plants during interglacial periods, whereas range expansion in cooler periods triggered dispersal to neighbouring regions. The range of C. kremeri expanded to the Iberian Peninsula by long‐distance dispersal across the Strait of Gibraltar during the Pleistocene. The relatively old age inferred for C. occidentalis together with its low genetic diversity point to a recent colonization of the Canary Islands from north‐west Africa followed by extinction in the mainland or an old lineage that underwent a recent genetic bottleneck.